Diseño de las obras de cruce del canal principal del proyecto: Irrigación Biavo margen izquierda - Rodriguez Guerra, Roger Augusto (2011)
the water resources of the Huallaga river will be captured through a pumping system, consisting of 09 electric pumps of 1.00 m3 / sec. capacity each; the waters will be conducted throughout the coverage area of ​​influence of the project through a main channel of 13.62 Km. in length, which it will be distributed through a system of side channels 35,54 km. long to 6250 ha. net to irrigate. The proposed infrastructure to meet the requirement of irrigation water, is comprised of the following major works: Power Station Sub- Energy supply Electromechanical equipment Pumping Plant Feeder Canal Main Canal Artworks Irrigation and Drainage System. Along the main channel they have been identified different places where crossing works that will ensure the continuity of the channel will be located. Also crossing works that will be necessary to build roads to facilitate communication between the irrigation area and production are located at a level above the main channel between these works have the following. TYPE SEWER ARMCO It is used in work underdrain low flow and installed in the natural course of streams the project consists of six (06) units.